Ethical standards for the occupational health-nursing practitioner regarding the HIV positive person in the workplace - Otto, M; Botes, A C (Health SA = SA Gesondheid, 2001)
The occupational health-nursing practitioner often becomes involved in ethical dilemmas with regard to the handling of HIV-positive people in the workplace in that the interests of the HIV-positive people conflict with the interests of the employer.OpsommingDie beroepsgesondheidsverpleegkundige raak dikwels in etiese dilemmas betrokke ten opsigte van die hantering van die MIV-positiewe persoon by die werkplek deurdat die belange van die MIV-positiewe persoon botsend is met die belange van die werkgewer. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.